(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2025)
This study examines the evolution of the chancery of the Judicate of Arborea through the figure of Pietro Pagano, a cleric active between 1182 and 1195. Initially referring to himself as indignus sacerdos, Pagano later adopted the title of kancellarius curie Arborensis, and, based on currently available sources, emerges as the first and only formally attested chancellor within a Sardinian judicial chancery. His activity is notable for the diversity of the surviving documentary corpus - composed in both Latin and Sardinian vernacular - and for the use of both local and continental diplomatic formulas. The analysis of the seven acts attributed to him reveals a high level of scribal competence, in marked contrast with the widespread illiteracy of the contemporary Arborensian clergy. Pietro Pagano’s work represents a turning point in the institutionalization of Sardinian chanceries, marking the transition from an informal documentary practice - typically entrusted to occasional clerics - to a more structured and professionalized bureaucratic model.